The act of reading as an instrument of human emancipation: importance of reading practices at school (Research, Society and Development, 2020)
Reading is an important habit that is closely linked to life in society. It is a way for the individual to relate to the world, allowing the development of critical sense, making him able to perceive the various voices that echo in the social debate. In this perspective, the act of reading becomes a tool for human emancipation. In this article, we seek to discuss the importance of reading practice for an emancipatory formation, starting from Freire's ideas that point to reading as an instrument of human emancipation and Vygotsky's theories, about the importance of social interaction for the appropriation of knowledge, emphasizing the role of the school in this process. This research has a qualitative approach, whose methodological option was bibliographic research, anchored in readings by authors who discuss the topic. It was possible to conclude that reading is an indispensable tool for the formation of critical and active subjects, and that the school has a fundamental role in the consolidation of reading practice.